Analisis Penerjemahan: Studi Kasus Pada Teks Eksplanasi Yang Berjudul Forest And Forestry Ke Bahasa Indonesia - Dellen Edson Augustino Pietersz; Ni Putu Meri Dewi Pendit (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
The translation method is expected to be a solution to the translation problems faced by translators. Translators are responsible for making accurate translated texts, writing and editing the translations so that they are easy to understand without changing the information contained in the source text. This scientific work is a case study on the translation of an article entitled Forest and Forestry that was sourced from the Open University BMP Translation 10, with the source text (ST) in English which was then translated into the target text (TT) in Indonesian. The case study method is used in this study to examine the results of the theoretical translation, and to find the translation method used to produce a translation that is commensurate and also acceptable. The Forest and Forestry article has several issues that make it more interesting to discuss in depth, including: limited word equivalents into TT, changes in the structure of TT to TT, and inconsistencies in the translation of certain words. There are three translation methods that are often used, including: word-for-word translation, failful translation, and literal.